Opportunities or threats? The role of entrepreneurial risk perception in shaping the entrepreneurial motivation - Liping Yin; Yenchun Jim Wu (Journal of Risk and Financial Management, 2023)
Entrepreneurial risk is an important factor that individuals must consider when starting their own business. The COVID-19 continues to rage, bringing great challenges to China's economy and entrepreneurial activities. In this study, college students encounter greater entrepreneurial risks. There are two opposing views on the role of entrepreneurial risk in shaping individual entrepreneurial motivation: one view that risk is a threat, and the other view that entrepreneurial risk contains opportunity. Existing studies have discussed the issues from individual factors and environment factors, respectively, ignoring the combined effects of individual and environment factors. Person-situation transactions theory points out that individuals usually make their final behavior choices based on their comprehensive evaluation of environmental factors and themselves. Therefore, individual and environment factors should be integrated to investigate the effect of entrepreneurial risk on entrepreneurial motivation. Based on the person-situation transactions theory, this study establishes a theoretical model that entrepreneurial risk perception influences necessity and opportunity entrepreneurial motivation through entrepreneurial self-efficacy and discusses the moderating effect of entrepreneurship policy. A questionnaire survey was conducted on 595 fresh graduates from eight universities in China to obtain relevant data and the Structural Equation modelling was established to test the hypothesis. The results confirm that without the influence of external factors, college students regard entrepreneurial risk as a great threat, which not only weakens their entrepreneurial self-efficacy, but also reduces their necessity and opportunity entrepreneurial motivation. However, with the support of good entrepreneurial policies, entrepreneurial risk can be transformed into an opportunity to improve the entrepreneurs motivation driven by necessity of college students, but the impact on the opportunity motivation is not significant. This study deeply analyzes the dual characteristics of entrepreneurial risk perception in the process of shaping individual entrepreneurial motivation, expands the related research on entrepreneurial risk perception and entrepreneurial motivation, and has important implications for the government and universities to formulate entrepreneurial policies for college students.
Keywords: 650; entrepreneurial motivation; entrepreneurial risk perception; entrepreneurial self-efficacy; entrepreneurs motivation driven by necessity; entrepreneurs motivation driven by opportunity; entrepreneurship policy